Belief Persistence after Evidential Discrediting: The Impact of Generated versus Provided Explanations on the Likelihood of Discredited Outcomes - Davies, Martin F. (Journal of experimental social psychology, 1997)
Belief persistence after evidential discrediting was examined as a function of generated vs provided explanations. In Experiment 1, subjects who generated explanations for event outcomes produced significantly more belief persistence after the outcomes were discredited than subjects who read provided explanations. These differences in belief persistence were not found under no-discrediting conditions. Because the findings could have been due to differences in perceived quality of generated vs provided explanations, Experiment 2 examined belief persistence using high-quality provided explanations. These provided explanations were judged to be better than generated explanations but belief persistence was still significantly greater for generated explanations. Experiment 3 replicated these findings with hypothetical outcomes. In addition, it was found that fewer contrary reasons were produced after generating explanations than after reading provided explanations for both hypothetical and discredited outcomes. The findings were discussed in terms of elaborative processing, generation effects, and output interference.